1984
DOI: 10.1111/j.1471-0528.1984.tb04765.x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of RNA complementary to HSV‐2 (herpes simplex virus) DNA in cervical intraepithelial neoplasia after laser therapy

Abstract: In-situ hybridization of radiolabelled DNA probes to tissue sections detected RNA complementary to HSV-2 (herpes simplex virus) DNA in 65% (22 of 34) biopsies from cervical intraepithelial neoplasia (CIN) and in none of internally paired benign epithelia from individuals before treatment by laser vaporization cone. Laser therapy did not produce an increase in clinical or subclinical HSV infections of the cervix. Of 18 patients with RNA complementary to HSV-2 DNA in CIN biopsies before treatment, in whom treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Chen and colleagues showed that cervical carcinoma could be induced in 50% of mice after repeated intravaginal inoculation with inactivated HSV-2 and that malignant transformation could be prevented by administration of a subunit vaccine [24]. However, studies utilizing immunocytochemical and DNA hybridization techniques have not consistently demonstrated HSV antigen or DNA in tumor tissue sampled from women with cervical carcinoma [25][26][27][28]. The role of HSV may be one of an initiator or enhancer of oncogenic transformation, possibly in combination with other factors.…”
Section: Natural History and Sequelae: Cervical Carcinomamentioning
confidence: 99%
“…Chen and colleagues showed that cervical carcinoma could be induced in 50% of mice after repeated intravaginal inoculation with inactivated HSV-2 and that malignant transformation could be prevented by administration of a subunit vaccine [24]. However, studies utilizing immunocytochemical and DNA hybridization techniques have not consistently demonstrated HSV antigen or DNA in tumor tissue sampled from women with cervical carcinoma [25][26][27][28]. The role of HSV may be one of an initiator or enhancer of oncogenic transformation, possibly in combination with other factors.…”
Section: Natural History and Sequelae: Cervical Carcinomamentioning
confidence: 99%